2019
DOI: 10.3390/en12163041
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement of TiO2/Water Nanofluids Flowing Inside a Square Minichannel with a Microfin Structure: A Numerical Investigation

Abstract: A combination of two passive heat transfer enhancement techniques using a microfin structure and nanofluids was investigated numerically. TiO2/water nanofluids flowing inside a square minichannel with a microfin structure (SMM) were observed as a practical application. Increased heat transfer performance was investigated by observing the Nusselt number, friction factor, and performance evaluation criterion (PEC). Velocity and temperature profiles were also demonstrated at a laminar developing flow regime. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 54 publications
0
17
0
2
Order By: Relevance
“…The results show that adding 10% copper nanoparticles to the water/glycol mixture can enhance the heat transfer of the medium by about 30%. Kristiawan et al [32] studied two passively enhanced heat transfer technologies combining a microchannel structure and a nanofluid by measuring Nusselt number, friction coefficient and heat transfer performance. It has been proven that, compared with water flowing in a square microchannel, using nanofluids with a volume fraction of 0.01% can increase the heat transfer efficiency of the microchannel.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that adding 10% copper nanoparticles to the water/glycol mixture can enhance the heat transfer of the medium by about 30%. Kristiawan et al [32] studied two passively enhanced heat transfer technologies combining a microchannel structure and a nanofluid by measuring Nusselt number, friction coefficient and heat transfer performance. It has been proven that, compared with water flowing in a square microchannel, using nanofluids with a volume fraction of 0.01% can increase the heat transfer efficiency of the microchannel.…”
Section: Introductionmentioning
confidence: 99%
“…That is, there are the advantages that a flow can be created only by a magnetic force without direct contact with the fluid, and that control is possible with a relatively simple configuration. In addition, it was confirmed that nanofluids have superior thermal performance compared to general fluid, due to the properties of the particles [4,5].…”
Section: Introductionmentioning
confidence: 89%
“…Other research has also shown that the overall composition of nanoparticles in the base fluid improves the overall heat transfer coefficient [30][31][32][33].…”
Section: Introductionmentioning
confidence: 94%